Inequalities in household overcrowding in an ethnically diverse urban population: a cross-sectional study using linked health and housing records - Marta Wilk; Gill Harper; Silvia Liverani; Nicola Firman; Paul Simon; Carol Dezateux (International Journal of Population Data Science)
Introduction Household overcrowding is an important determinant of health and is associated with adverse child health, educational and social outcomes.